Motivations for corporate social responsibility practices in Singapore shipping companies part I - environmental aspect of CSR - Mohamad Kamaluddin. (2011)
The shipping industry represents the most regulated industry with various regulatory bodies recommending adherence to regulations relating to maritime safety, security, welfare and governance. The regulatory implementations along with the dynamic and cyclical nature of the business, entails a constantly changing competitive landscape for industry practitioners. Recent changes have come in the form of CSR. CSR is a management concept that is the commitment of business to contribute to sustainable economic development so that quality of life improves. Although there has been a strong positive uptake of CSR amongst shipping companies, the motivation behind these undertakings have yet to be known. Therefore, the purpose of this report is to find out the motivation for CSR practices in Singapore Shipping companies. More specifically, the author of this report will investigate into the Environmental Aspects of CSR.